Raw data of Cenozoic coccolith Feret's diameter from the Atlantic Ocean - Barrett, Ruby; Power, Ann (PANGAEA, 2025)
This dataset contains the size measurement (μm) for each individual coccolith analysed in the sample for the Atlantic Ocean Sites DSDP 80-548 and ODP 154-925 and 154-929, spanning the Cenozoic (~0 to 66 Ma). Coccolith size data were acquired from images taken using an ImageStream X MkII flow cytometer with a light polarising filter and include circular-to-oval shaped coccoliths and star-shaped coccoliths. This dataset can be used to investigate how coccolith size of the aforementioned types changes through the Cenozoic.